Coastal corals during heat stress and eutrophication: A case study in Northwest Hainan coastal areas. (December 2021) - Zhu, Wentao; Xia, Jingquan; Ren, Yuxiao; Xie, Minrui; Yin, Hongyang; Liu, Xiangbo; Huang, Jianzhong; Zhu, Ming; Li, Xiubao
Abstract: This study initially investigated the coral status during the unexpected bleaching event in three coastal areas in Northwest Hainan coastal areas and analyzed changes in coral holobionts of the healthy and bleached Galaxea fascicularis . Coral coverage had declined severely, and the bleaching rate was extremely high during heat stress. The bleached corals had lower maximum photosynthetic yield, actual photosynthetic yield, zooxanthellae density, and chlorophyll a content than the healthy G . fascicularis, but there was no significant difference in protein, carbohydrate and lipid in eutrophic waters. The diversity and community composition of Symbiodiniaceae and symbiotic bacteria between healthy and bleached G . fascicularis showed no difference. Function prediction of the symbiotic bacteria revealed that the metabolism process was the main pathway of annotation. Present findings suggested that energy reserve functioning and high stability of the holobiont structure and might provide opportunities to G . fascicularis to adapt to eutrophication and heat stress. Graphical abstract: Unlabelled Image Highlights: Changes in coral community and holobionts under eutrophication and bleaching events were studied. Bleached corals maintained some photosynthetic capacity in moderate nutrient concentrations and heat stress. Energy storage of bleaching Galaxea fascicularis in eutrophic waters was not reduced due to strong heterotrophy ability. Stable community structure of Symbiodiniaceae and microbiota potentially favoring the survival of G . fascicularis .